Orbis imagines, tool for research and dissemination of engraving in Andalusia (16th-18th) - Escalera Pérez, Reyes (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
There are numerous and varied investigations that analyze the art of engraving in Andalusia in the Modern Age, its influence on artistic works, as well as the mastery of some of its creators. However, we do not have a work that unites all these areas, hence the need for the project that we present called “Three centuries of engraving art (16th-28th): print and visual culture in Andalusia and its impact on the New Word. New approaches” whose objective, in addition to the research that includes a rereading of said phenomenon, is the creation of the “Orbis imagines” platform.